2013
DOI: 10.1159/000354962
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline Predicts Long-Term Care Insurance Requirement Certification in Community-Dwelling Older Japanese Adults: A Prospective Cohort Study

Abstract: Aim: The purpose of this prospective cohort study is to examine whether cognitive decline is an independent predictor of new long-term care insurance (LTCI) requirement certifications in Japan. Methods: A total of 5,765 community-dwelling older Japanese adults who, at baseline, were independent in terms of their activities of daily living participated in this study and were followed up for 18 months. The outcome measure was the number of new LTCI requirement certifications during the 18-month period of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…First, assessing “cognitive function” is regarded to be of high importance for community‐dwelling older adults. Several previous studies showed lower cognitive status was closely associated with overall diminished functioning, the development of dementia and newly certified older adults under the LTCI …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…First, assessing “cognitive function” is regarded to be of high importance for community‐dwelling older adults. Several previous studies showed lower cognitive status was closely associated with overall diminished functioning, the development of dementia and newly certified older adults under the LTCI …”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies showed lower cognitive status was closely associated with overall diminished functioning, the development of dementia and newly certified older adults under the LTCI. 7,[23][24][25] Second, in 2012, Japanese MHLW notified all local governments of a 5-year plan, the so called "Orange Plan," for people with dementia to be detected early, to be treated and to be cared for suitably, not only in hospital, but also by community-based support. This notification by MHLW is of importance for Japanese local governments and communities as well as academic societies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some individuals retain a high level of cognitive ability from mid- to late- life, others may experience decline [ 5 ]. A decline in cognitive function can be detrimental to the independence, wellbeing, and quality of life of older people [ 6 , 7 ]. Understanding the mechanisms underlying differences in cognitive ageing is important to reduce the impact of poor cognitive function in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of cognitive functioning was conducted using the Cognitive Performance Scale [ 33 ]; the total score ranges from 0 to 6, with higher scores expressing a lower level of cognitive functioning. Because a prior study has demonstrated that a score ≥ 1 in the Cognitive Performance Scale can predict the onset of functional disability in community-dwelling older Japanese people [ 34 ], we defined a score of 0 as subjects with intact cognitive functioning, and scores of ≥1 as subjects with poor cognitive functioning. Assessment of depression was conducted using the 5-item short form of the Geriatric Depression Scale [ 35 ]; the total score ranges from 0 to 5, with higher scores defined as more depressed.…”
Section: Methodsmentioning
confidence: 99%